BUILDING QUALITY ASSURANCE AND CONTRACTOR LIABILITY IN REAL ESTATE HOUSES ACCORDING TO IJÂRAH 'ALA AL-'AMÂL - Rezkia, Fitra; Reza, Teuku Surya (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This article aims to examine the quality assurance of buildings with a piecework system and contractor coverage on real estate houses according to ijârah 'ala al-'amâl. The type of research used is descriptive with a normative sociological approach. Data collection techniques through interviews, documentation, data analysis. The results showed that the occurrence of several post-development damage factors such as material quality, construction errors, extreme environmental conditions. So that it can affect the occurrence of damage to buildings such as damage; structural and non-structural, due to environmental factors, utility systems, improper use and maintenance, humidity, unauthorized structural changes, finishing, exterior and landscape areas, due to natural disasters. Contractor building quality assurance is fully responsible starting from complying with regulations and guidelines, during the construction period the contractor always conducts supervision / inspection on a scale and after the work is completed the contractor repairs defects or damage that arise due to errors in implementation during the construction period. Ijârah 'ala al-'amâl regulates the reciprocal relationship between the parties and the reward in accordance with the agreement, the concept of ijârah 'ala al-'amâl emphasizes to pay attention to the level of quality that must be met and encourages workers to commit to maintaining it. The concept of ijârah 'ala al-'amâl as a whole offers a more structured framework and can provide a stronger foundation for developers to demand the fulfillment of quality standards because the work contract in the context of ijârah 'ala al-'amâl is directed based on the principles of Islamic law and has high legitimacy so as to provide better legal certainty.